Potential Of Mahkota Dewa Fruit (Phaleria macrocarpa) Flavonoids Extract and Dienogest to Reduce IL-17A Levels in Mice Endometriosis Model - Ana Paramita Prastiwi; Leni Ria Ariana; Gema Alya Salsabila; Sutrisno Sutrisno; Nurdiana Nurdiana; Nanik Setijowati; I Wayan Agung Indrawan (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Endometriosis is an inflammatory disease that occurs in glands outside the endometrium. Interleukin 17 (IL-17) is a proinflammatory cytokine degrading Th17 cells, which play an essential role in several inflammatory diseases. IL-17 expression is upregulated in serum, peritoneal fluid (PF), and endometriotic lesions from patients with endometriosis. Usually, treatment for endometriosis is dienogest. However, it has many side effects if used long-term. Fruit and seeds of Phaleria macrocarpa have various critical biological activities in the form of extracts such as antimicrobial, anti-inflammatory, and antioxidant activities. This study aims to analyze the effect of comparing flavonoid fruit extract of Phaleria macrocarpa and dienogest on IL-17A levels in endometriosis mice. A total of 35 endometriosis model mice were divided into seven groups, namely the group of healthy mice (without any treatment), the endometriosis group, and the endometriosis group, which were given the treatment of flavonoid fruit extracts of Phaleria macrocarpa and dienogest. The sample used in this study was peritoneal fluid. The enzyme-linked immunosorbent assay (ELISA) measured IL-17A levels in each observation group. The hypothesis was tested using One-Way ANOVA analysis with SPSS software version 26. This study found a significant difference (p<0.05) between the mean values of the positive control group and the negative control group. There was also a significant difference (p<0.05) in the mean value IL-17 between the treatment groups that were given sphalerite macrocarpa and dienogest extracts. Flavonoid fruit extract of Phaleria macrocarpa had a significant effect on reducing IL-17A levels in endometriosis model mice, and there is a significant difference with dienogest. Thus, the flavonoid fruit extract of Phaleria macrocarpa can potentially treat endometriosis by decreasing inflammatory factors.